2022
DOI: 10.3389/fimmu.2022.920666
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related gene signature associates with immune landscape and predicts prognosis accurately in patients with Wilms tumour

Abstract: Wilms tumour (WT) is the most common kidney malignancy in children. Chemoresistance is the leading cause of tumour recurrence and poses a substantial therapeutic challenge. Increasing evidence has underscored the role of the tumour immune microenvironment (TIM) in cancers and the potential for immunotherapy to improve prognosis. There remain no reliable molecular markers for reflecting the immune landscape and predicting patient survival in WT. Here, we examine differences in gene expression by high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Some studies have compared the differences of immune cells in tumor microenvironment between WT high-risk group and low-risk group. In the high-risk group, it was found that except for B cells and macrophage M1 type, other types of cells were lower than those in the low-risk group, including CD8 + naive T cells, CD8 + T cells, macrophage M2 type, mast cells, neutrophils, NKT cells and Treg cells [39]. This suggests that the high-risk WT tumor microenvironment as a whole exist immune inactivation and lack of T cells.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have compared the differences of immune cells in tumor microenvironment between WT high-risk group and low-risk group. In the high-risk group, it was found that except for B cells and macrophage M1 type, other types of cells were lower than those in the low-risk group, including CD8 + naive T cells, CD8 + T cells, macrophage M2 type, mast cells, neutrophils, NKT cells and Treg cells [39]. This suggests that the high-risk WT tumor microenvironment as a whole exist immune inactivation and lack of T cells.…”
Section: Discussionmentioning
confidence: 91%
“…A large number of existing studies have shown that the tumor microenvironment can not only in uence tumor cell growth and metastasis, but also has great importance in therapy [39][40][41] , in particular, the association between TME and methylation modi cations and the in uence of TME on tumor progression in WT has been reported 42,43 . We quanti ed the in ltration of 29 different immune cell types in WT samples by ssGSEA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Their research suggested that impaired anti-tumor immunity may be responsible for the poor prognosis of WT patients at high risk. Research into the mechanisms that disrupt the anti-tumor immune response will contribute to the development of more effective treatments 66 .…”
Section: Discussionmentioning
confidence: 99%